Clinical significance of subclinical carotid atherosclerosis and its relationship with echocardiographic parameters in non-diabetic chronic kidney disease patients - Kim, Jwa-Kyung (BMC Cardiovasc Disord, 2013)
BACKGROUND: Non-diabetic chronic kidney disease (CKD) patients are a heterogeneous group with a variety of prognosis. We investigated the role of subclinical carotid atherosclerosis for the prediction of adverse cardiovascular (CV) outcomes in these patients, and tried to identify clinical and echocardiographic parameters associated with subclinical carotid atherosclerosis. METHODS: As a prospective design, 182 asymptomatic non-diabetic CKD patients underwent carotid ultrasonography and Doppler echocardiography. Carotid atherosclerosis was defined as a carotid intima-media thickness ≥1.0 mm and/or the presence of plaque. RESULTS: During the mean follow-up period of 28.8 ± 16.1 months, 23 adverse CV events occurred. Patients with carotid atherosclerosis (99, 54.4%) showed significantly higher rates of annual CV events than those without (8.6 vs. 1.5%, p <0.001). Particularly, the presence of carotid plaque was a powerful predictor of adverse CV outcomes (OR 7.80, 95% CI 1.45-45.97). Clinical parameters associated with the presence of subclinical carotid atherosclerosis were old age, previous history of hypertension, increased pulse pressure, and higher high-sensitivity C-reactive protein (hs-CRP) level. By echocardiography, early diastolic mitral annular velocity (E’) and the ratio of early peak transmitral inflow velocity (E) to E’ (E/E’) were closely related with the presence of carotid atherosclerosis. A multivariate analysis showed that age, hs-CRP, and E/E’ were significant determinants of carotid atherosclerosis. CONCLUSIONS: Carotid plaque, even subclinical, was closely associated with a poor prognosis in non-diabetic CKD patients. Increased age, hs-CRP level, and E/E’ ratio may be useful markers suggesting the presence of carotid atherosclerosis in these patients.